The arginase pathway of L-arginine metabolism of peripheral blood lymphocytes in patients with acne vulgaris - G. S. Lavryk; O. P. Korniychuk; A. S. Besedina; Z. D. Vorobets (Regulatory Mechanisms in Biosystems, 2017)
The mechanisms of development of the inflammatory process of the pilosebaceous apparatus in patients with acnе vulgaris are not fully understood, and variations in bacterial colonization are one of the key elements of the inflammatory process. Under the pathological conditions caused by pus-forming cocci which induce the production of proinflammatory cytokines, there is an increase in arginase expression. The capacity for film formation in selected strains was determined by the cultural properties (increased viscosity of the colony biomass) and by differential interference contrast microscopy using a dark field condenser and fluorescence microscopy. Arginase activity (μmole urea/min•mg of protein) was determined spectrophotometrically at 520 nm on saponin-perimabilized lymphocytes of peripheral blood by the rate of urea formation. The cultures of film-forming and planktonic forms of Staphylococcus epidermidis and Staphylococcus aureus were isolated from purulent pustules of 44 patients, aged 18–30. 63.6% of clinical strains of film-forming staphylococci were isolated, out of which 15 strains (53.6%) were S. aureus and 13 strains (46.4%) S. epidermidias. It was found that the arginase activity in patients (film-forming S. aureus) was significantly higher than in practically healthy donors (control) and was equal to 0.262 ± 0.006 and 0.279 ± 0.005 (planktonic form of S. aureus) versus 0.087 ± 0.009 μmole urea / min∙mg of protein in the control. The arginase activity in patients (film-forming S. epidermidis) was significantly higher than in practically healthy donors and was equal to 0.281 ± 0.009 and 0.297 ± 0.006 (planktonic form of S. epidermidis) versus 0.087 ± 0.009 μmol urea / min∙mg of protein in the control. After the auto-vaccine therapy and the administration of the probiotic Lacidofil (Institut Rosell Inc., Canada), enzyme activity decreased significantly in both experiments, however it had not attained control levels. The enzyme activity decreased through the administration of a vaccine, which in turn has an immunomodulating and immunostimulating effect. In addition, comparing the data of the arginase activity after treatment in patients with S. epidermidis, there was a slight decrease in the enzyme activity. This result is probably due to the formed tolerance of the immune system to commensal microorganisms. It was found that all patients had a moderate dysbiosis, which was accompanied by a deficiency of the main normal symbionts of the intestine. After treatment, all patients experienced significant improvementst in the microbiocenosis of the intestine in the direction of normalization of parameters and improvement of the skin condition. Increase in arginase activity in patients with acne vulgaris indicates the competition of this enzyme with NO-synthases for the substrate L-arginine and the alteration of physiological reactions in the organism caused by staphylococci which induce the phagocytic response and the cytokines production of the humoral system.